PENGARUH WORK LIFE BALANCE DAN BURNOUT TERHADAP KEPUASAN KERJA PERAWAT RSUD M. YUNUS KOTA BENGKULU - Sartika, Liza; Onsardi, Onsardi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
The purpose of this study was to determine the effect of work-life balance and burnout on job satisfaction among nurses at M. Yunus Regional General Hospital, Bengkulu. This study was a quantitative descriptive study, with all nurses at M. Yunus Regional General Hospital as the research subjects. Data collection techniques used were observation, interviews, and questionnaires. Data analysis techniques used descriptive analysis, inferential analysis using SPSS, and coefficient of determination (R2) analysis. The results showed that work-life balance significantly influenced job satisfaction among nurses at M. Yunus Regional General Hospital, Bengkulu. The better the work-life balance, the higher the nurses' job satisfaction. Burnout had a positive and significant effect on job satisfaction among nurses at M. Yunus Regional General Hospital, Bengkulu. Emotional, mental, and physical fatigue conditions that can be managed well will have an impact on increasing job satisfaction. Work life balance and burnout simultaneously or together have a positive and significant effect on job satisfaction of nurses at M.YUNUS Bengkulu Regional Hospital. This shows that the balance between nurses' personal life and work not only affects job satisfaction, but also the nurses' ability to manage physical, emotional, and mental fatigue.. Kelywords: Work Lifel Balancel, Burnout, Job satisfacation